V.1 - Jayapalan, N. (New Delhi, 2001)
The book deals with all aspects of the 'Indian Society and Social Institutions' in detail. The Characteristics of Indian Society, Indian Culture, Values of Indian Social System, Hindu Social Organisation and the Caste System have been described in the first five chapters with enormous facts so as to meet the requirements of the students. The book also provides a good picture of the Casteism, Untouchability, the Hindu Family System, Muslim Social System, Christian Social System, Tribal Social System and Rural Problems in India along with Social Legislations and Status of Women in Hindu Society from sixth chapter to twenty fifth chapter. The remaining chapters i.e., twenty six to forty give a descriptive account of Social Disorganisation, Sanskritization, Westernisation, Secularisation, Modernisation, Condition of Housing, Education and Industrial Workers, Trade Unions, Indian Political System and the Role of Religion in Politics. In brief, sufficient informations have been given in an elaborate way in the book regarding 'Indian Society and Social Institutions' so as to meet the requirements of the students and the common readers.
Keywords: Society-India